Evaluasi Kinerja KAPET (Kawasan Pengembangan Ekonomi Terpadu) Palapas Dalam Mendorong Pertumbuhan Ekonomi di Provinsi Sulawesi Tengah - Widjonarko, Widjonarko (Magister Pembangunan Wilayah dan Kota,Undip, 2013)
KAPET (Kawasan Pengembangan Ekonomi Terpadu or Integrated Econonic Development Zone - IEDZ) is a government driven program to boost economic development in eastern Indonesia. The program was launched during the period of President Suharto’s administration in 1996 and was finalized in 1998 through Presidential Decree No. 9 year 1998. IEDZ Palapas is one of the IEDZs developed in Sulawesi Island, and is located in Central Sulawesi Province. IEDZ Palapas is proposed to substitute the former IEDZ Batui in the Central Sulawesi. IEDZ Palapas effectively started its operation in 2008. The Development of IEDZ Palapas was aimed to promote economic growth in the Central Sulawesi with Palu City as the center of regional development. The study evaluates the performance of IEDZ Palapas through examination of macroeconomic indicators as derivative products from the Gross Domestic Product in Central Sulawesi Province. The evaluation process has shown that for the past four years, the establishment of IEDZ Palapas has not been able to provide the driving force for economic growth in Central Sulawesi Province.